From sea to land. An all-encompassing approach - Giuseppina Maddaluno; Giacomo Mascoli (Freedom from Fear, 2009)
Contemporary piracy is a booming criminal activity, not only because of its high profitability with an extremely positive cost-benefit balance for the perpetrators, but also due to the acute vulnerability of the targets, lack of awareness and specific countermeasures along with the highly underreported nature of the crime. Since the beginning of 2008 UNICRI started to develop the idea of a programme taking into account the Institute’s competences in crime prevention and knowledge management, and its expertise in the establishment of an effective public / private partnership to counter crime. The programme has been conceived within the framework of the UN convention on the Law of the Sea (1982) and on the Convention for the Suppression of Unlawful Acts Against the Safety of Maritime Navigation (1988), considering also the United Nations Security Council Resolutions 1816, 1846 and 1851 (2008), which authorize a series of decisive measures to combat the acts of piracy against vessels off the coast of Somalia.